2020
DOI: 10.3847/2041-8213/ab85c5
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Model for the Multiwavelength Lightcurves of PSR J0030+0451

Abstract: Recent modeling of Neutron Star Interior Composition Explorer (NICER) observations of the millisecond pulsar PSR J0030+0451 suggests that the magnetic field of the pulsar is non-dipolar. We construct a magnetic field configuration where foot points of the open field lines closely resemble the hotspot configuration from NICER observations. Using this magnetic field as input, we perform forcefree simulations of the magnetosphere of PSR J0030+0451, showing the three-dimensional structure of its plasma-filled magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…By comparing the observed ∆ − δ diagram with their estimations from the model, these authors favoured the cases with high conductivities; as the conductivity increases, the system converges to the FFE limit. Chen et al (2020) recently suggested a force-free magnetospheric model and presented radio, X-ray, and gamma-ray light curves in agreement with the observations of the millisecond pulsar (MSP) PSR J0030+0451, providing an estimation of the magnetic inclination of the pulsar of ∼80 • . More recently, Kalapotharakos et al (2020) proposed the FFE model by taking into account an off-centred dipole field and quadrupole components, the Kerr-metric for the ray-tracing of photons from a distant observer to the hot spots on the surface of the star.…”
Section: Introductionsupporting
confidence: 61%
“…By comparing the observed ∆ − δ diagram with their estimations from the model, these authors favoured the cases with high conductivities; as the conductivity increases, the system converges to the FFE limit. Chen et al (2020) recently suggested a force-free magnetospheric model and presented radio, X-ray, and gamma-ray light curves in agreement with the observations of the millisecond pulsar (MSP) PSR J0030+0451, providing an estimation of the magnetic inclination of the pulsar of ∼80 • . More recently, Kalapotharakos et al (2020) proposed the FFE model by taking into account an off-centred dipole field and quadrupole components, the Kerr-metric for the ray-tracing of photons from a distant observer to the hot spots on the surface of the star.…”
Section: Introductionsupporting
confidence: 61%
“…Pair production in relation to the coherent emission of millisecond pulsars (MSP) is a subject that has received little attention, but is now of increased interest as a consequence of the NICER J0030+0451 observations (Riley et al 2019, Miller et al 2019, Bilous et al 2019. These provide the first evidence for a quadrupole component in the surface magnetic flux density whose properties have been further analysed by Chen, Yuan & Vasilopoulos (2020) and Kalapotharakos et al (2021).…”
Section: Introductionmentioning
confidence: 71%
“…The preferred configuration of the temperature distribution for PSR J0030+0451 found by the independent analyses of Miller et al (2019) and Riley et al (2019) consists of one highly elongated (in the longitudinal direction) region and a second smaller, less elongated region, both on the hemisphere below the stellar equator relative to the observer's line of sight. Such a temperature distribution is difficult to reconcile with a standard dipole field, but could be reproduced by assuming a dipole+quadrupole field 2 (see, e.g., Gralla et al 2017;Lockhart et al 2019;Chen et al 2020;Kalapotharakos et al 2021). In such a case, the strength of the surface magnetic field inferred using a magnetic dipole braking formula could substantially underestimate the strength of the magnetic field within the atmospheres of hot spots (see Miller et al 2019).…”
Section: Neutron Star Model Atmospheresmentioning
confidence: 99%